Physioterapy in a child shelter: An experience report of an extension project - Sin Singer Brugiollo, Alessa; Martins Coelho, Cristina; Palermo Ferreira, Mariana Cristina; Miranda Máltaro, Caroline; Pereira Braga, Sara; Ribeiro dos Santos, Ruth Ellen; de Viveiros Gomes, Daniela; Defilipo, Erica Cesário (Guará Journal, 2018)
Child  shelters  have  often  been  cited  as  sites  of negative  impact  on  neuromotor  development  and are important  risk  factors  for  acute  respiratory  infections in  this  population.  In  this  way,  the  monitoring  of the neuromotor development and the ventilatory function of children  living  in  shelter  institutions  should  be prioritized,  with  actions  to prevent and promote health. The aim of this study is to report the experience of physical therapist undergraduates’ students in a child care  institution  in  the  city  of  Governador  Valadares, Minas  Gerais.  This project consisted in evaluating the motor development and the ventilatory  function  of infants  and  children,  providing  physiotherapeutic care and  orientations  to  caregivers.  The  experience  at  the shelter allowed physical therapist undergraduates’ students to inte-grate  teaching  with  practice  through physical  therapy  assessment  and treatment in pediatrics, early identification of risk factors related to institutionalization and detection of delays in motor development and respiratory signs and symptoms.
Keywords: Physical therapy specialty; Orphanages; Child development; Respiratory therapy